Prosedur Pengembangan Bahan Ajar Pendidikan Agama Islam (PAI) - Maksum, Muh. (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
The development of quality and effective Islamic Religious Education (PAI) teaching materials is the key to achieving optimal learning goals. This article discusses procedures for developing PAI teaching materials that are systematic and comprehensive, including five main stages: (1) needs analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. Each stage is explained in detail with concrete steps and applicable examples. It is hoped that this article can help teachers and PAI teaching material developers in producing quality teaching materials that suit the needs of students.